The results of studies of the buried complexes of the Babisch mole oasis (Journal of history, 2022)
The article describes the results of archaeological excavations of mausoleums No. 1 and 2 of the Akshukur and Egistik groups located in the lower reaches of the Syr Darya in the BabishMola oasis. During the excavations in the mausoleum, along with human remains, animal bones, ceramic and wooden dishes, tools, jewelry, weapons were found. All the discovered archaeological materials were compared with similar finds in other burials to identify similarities and identify differences. To analyze the anthropological material, the methods of craniometric measurements were used, which are widely used by researchers from near and far abroad. When studying the collection of animal bones, the archaeozoological approach was used as the main one, which allowed both to analyze and describe the elements of the skeleton of each animal, and the processes of fragmentation of these elements. In 2019-2020, excavations of mausoleums carried out indicate that a significant part of the objects were reconstructed and repeatedly used for burial. Funeral rites were also performed on wooden coffins and stretchers. Valuable and rich archaeological materials, such as ceramics, wooden utensils, weapons, household and jewelry, obtained during the excavations, will become a new source of information about the funeral rites of the inhabitants of the Babish Mola oasis. Key words: Chirikrabat culture, Babishmola oasis, mausoleum, anthropology, archeology, archaeological materials.